Ambivalence of trust and distrust : an exploratory study of a foreign invested enterprise in China - Wan, Stephen Kin Meng (2008)
This project applies a grounded theory building approach to examine the trust and distrust issues of managing in China within an organizational context. It explores and substantiates ambivalence of the phenomenon through a framework linking antecedents, manifestations, policies/measures and the outcomes.